Topologically Enhanced Cation–π Interactions for Developing High‐Performance Underwater Adhesive. Issue 12 (17th October 2022) - Pang, Huiwen; Yu, Rong; Huang, Anmin; Li, Xiang; Xu, Zenghui; Yin, Shulin
Abstract: Cation– π interactions provide an excellent way to develop high‐performance underwater adhesives. Although numerous underwater adhesive systems are designed based on cation– π interactions, they still lack precise design of the adhesive polymer backbone and topological control of the adhesive polymer. In this study, a novel short‐chain adhesive polymer with excellent underwater adhesion is developed based on the topologically enhanced cation– π interactions. Dihydrocaffeic acid containing catechol is incorporated into a short‐chain cationic polymer of polycarbodiimides through the nucleophilic reactions between carboxyl and carbodiimide groups to produce a catechol‐decorated cationic adhesive polymer (CCAP). The unique molecular structure of the CCAP confers the adhesive system strong cohesion and topologically enhanced cation– π interactions, leading to excellent underwater adhesion. Fe 3+ is introduced into the adhesive system to promote the coordination of catechol and the oxidative crosslinking of catechol to further improve the cohesion of the CCAP. In addition, based on the synergy between reversible noncovalent bonds and the irreversible oxidative crosslinking system, the prepared adhesive can also act as a high‐strength hot‐melt adhesive, which maintains nearly 90% of its adhesion strength after 10 attachment–detachment cycles, showing its great potential for use as a sustainable reusable dismountable adhesive. This study provides a novel strategy to develop high‐performance underwater adhesive with temperature sensitivity. Abstract : A novel underwater adhesive of catechol‐decorated cationic adhesive polymer (CCAP) is constructed based on topologically enhanced cation– π interactions. The prepared CCAP adhesive exhibits excellent underwater adhesion, showing outstanding adhesion on various substrate surfaces, including polytetrafluoroethylene, wood, and steel. Furthermore, the fabricated adhesive also behaves as a hot‐melt, presenting great potential for use as a reusable dismountable adhesive.